2022
DOI: 10.1200/jco.21.01715
|View full text |Cite
|
Sign up to set email alerts
|

Managing Central Nervous System Spread of Lung Cancer: The State of the Art

Abstract: Brain metastases (BrM) are common in both non–small-cell lung cancer and small-cell lung cancer. Substantial progress in BrM management has occurred in the past decade related to advances in both radiation and medical oncology. Recent and ongoing radiation trials have focused on increasing the candidacy for focal therapy of BrM with stereotactic radiosurgery; reducing the toxicity and improving patient selection for whole brain radiotherapy; and, in small-cell lung cancer, evaluating brain magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 138 publications
0
29
0
Order By: Relevance
“…All PFS and OS analyses were presented using HR and its 95% confidence interval. Heterogeneity analysis was performed using the I 2 test, with I 2 ≤ 50% representing low heterogeneity, and a fixed-effects model method was used for meta-analysis. I 2 > 50% represented significant heterogeneity, and the random effects model method was used for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…All PFS and OS analyses were presented using HR and its 95% confidence interval. Heterogeneity analysis was performed using the I 2 test, with I 2 ≤ 50% representing low heterogeneity, and a fixed-effects model method was used for meta-analysis. I 2 > 50% represented significant heterogeneity, and the random effects model method was used for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the existing data establishing the CNS activity of TKI in oncogenic addicted NSCLC is derived from trials not designed to robustly generate such data, as baseline screening for brain metastases was not always mandated and stratification often did not occur. 115,117 With the firstgeneration EGFR inhibitors such as erlotinib, gefitinib, and icotinib, CNS relapses occurred frequently due to pharmacologic failure as blood-brain barrier penetration of these TKIs is poor. Data for second-generation EGFR-TKIs is scarce and lacking for dacomitinib but suggests a higher intracranial activity compared with first-generation EGFR-TKIs.…”
Section: Systemic Treatment Of Nsclc Brain Metastasesmentioning
confidence: 99%
“…Moreover, there is increasing evidence that molecular targeted therapies or immunotherapy can treat BM [ 44 ]. Multiple clinical trials demonstrated that the central nervous system objective response rates are > 50% when using newer generation tyrosine kinase inhibitors, and treatment strategies involving upfront central nervous system active tyrosine kinase inhibitors alone with close magnetic resonance imaging surveillance may be considered for some patients with asymptomatic BM [ 45 ]. Therefore, unsympathetic patients who are adaptable to systemic therapy may be suitable for systemic therapy before re-WBRT is considered.…”
Section: Toxicitiesmentioning
confidence: 99%